The impact of digitalization on forming modern youth political leadership - O. A. Sudorgin; A. V. Agafonov (Управление)
Youth political engagement is a crucial aspect of modern society. In this regard, digitalization opens huge communicative and mobilization opportunities by transforming young people’s political participation into a digital format with unpredictable consequences. The article analyzes digitalization impact as a complex multi-stage process in modern world on forming youth political leadership. The essence and stages of digitalization, the consequences of digital technologies impact on society, political processes, and youth environment have been studied. The transformational impact on socialization, communicative culture and self-consciousness of youth as a fundamental basis for forming its most active part – youth political leaders – has been revealed. The authors consider how the use of digital means of communication, social networks, and digital ecosystems contributes to the activation of youth participation in political life, accelerates the process of forming youth political leaders, providing their “promotion” in the online space and supporters mobilization. Challenges and threats of digitalization faced by youth and young political leaders have been considered. The authors concluded that digitalization at the present stage is the most important condition for attracting and forming youth political leadership, but this aspect requires further study and support at the public policy level.